2015
DOI: 10.1002/pssa.201431829
|View full text |Cite
|
Sign up to set email alerts
|

Fully flexible and transparent piezoelectric touch sensors based on ZnO nanowires and BaTiO3 -added SiO2 capping layers

Abstract: We report on fully flexible and transparent piezoelectric touch sensors based on ZnO nanowires (NWs). Their piezoelectric properties are further enhanced by incorporating BaTiO3 into the capping layer on nanowires. Flexibility is improved by a highly transparent carbon nanotubes–silver nanowires electrode. A BaTiO3‐based capping layer on ZnO nanowires demonstrates a large increase of the output voltage (∼3.3 V) from the touch sensor compared to the voltage (∼50 mV). Mechanical bending tests reveal that the BaT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Commonly used piezoelectric materials can be divided into two categories: inorganic (eg, lead zirconate titanate, ZnO, and BaTiO 3 ) and organic (eg, polyvinylidene fluoride [PVDF], P(VDF‐TrFE)). Inorganic piezoelectric materials exhibit high sensitivity but low flexibility.…”
Section: Skin‐inspired Mechanical Sensorsmentioning
confidence: 99%
“…Commonly used piezoelectric materials can be divided into two categories: inorganic (eg, lead zirconate titanate, ZnO, and BaTiO 3 ) and organic (eg, polyvinylidene fluoride [PVDF], P(VDF‐TrFE)). Inorganic piezoelectric materials exhibit high sensitivity but low flexibility.…”
Section: Skin‐inspired Mechanical Sensorsmentioning
confidence: 99%
“…Perovskite piezoelectric materials such as BaTiO 3 are more appealing than ZnO due to their higher piezoelectric constants (Kang et al, 2015; Park et al, 2010). Park et al (2010) reported on a nano harvesters where the integration of BaTiO 3 into thin film formats on substrates was made with soft lithography and transfer printing.…”
Section: Inorganic Piezoelectric Devices In Biomedicinementioning
confidence: 99%
“…Piezoelectric devices based on ZnO NWs and capping layers of BaTiO 3 were used by Kang et al (2015) as touch sensors. This is illustrated in Figure 8(a).…”
Section: Inorganic Piezoelectric Devices In Biomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…A high piezoelectric constant and a low dielectric constant are essential to achieve high sensitivity for piezoelectric MEMS-based devices [14]. Among various piezoelectric thin films, such as aluminum nitride (AlN) [15], ZnO [16], BaTiO 3 [17], lead zirconate titanate (Pb(Zr,Ti)O 3 , PZT) [18] and polyvinylidenefluoride (PVDF) [19], PZT is the most popular due to its high piezoelectric constant, high energy density, and large electrical-mechanical coupling coefficients [12,20]. However, the pressure/touch sensitivity of thin film PZT with regard to voltage response is slightly smaller than that of AlN [21] because of a large dielectric constant-two orders of magnitude higher than that of AlN.…”
Section: Introductionmentioning
confidence: 99%